Gametophytic phase of three taxa of Anemia (Anemiaceae) - Chambi, Cristina Janet; Martínez, Olga Gladys (Instituto de Ecología, A.C., 2020)
Background and Aims: Anemiaceae has a single genus, Anemia, with 115 species distributed in the Neotropics, Africa, India, and islands in the Indian Ocean. The aim of this work is characterize living spores and gametophytic phase of three Anemia taxa from South America, little studied or with fragmentary studies, A. herzogii, A. tomentosa var. anthriscifolia and A. tomentosa var. tomentosa.Methods: Gametophytes of the three taxa have been obtained through in vitro cultures of spores. The spores and gametophytes were studied with light and scanning electron microscopes. The germination pattern of the spores, the evolution of the gametophytic development and the sexual expression were described.Key results: Filamentous gametophytes were formed by 4-20 cells, the adults were cordate, symmetrical or asymmetrical, bisexual and protandric, on their surfaces and margins clavate trichomes were observed. Gametangia corresponded to the leptosporangiate type. The dehiscence of antheridia was produced by a perforation in the opercular cell. Archegonia had necks with four to seven cells and four triangular cells at the distal end of the neck. Anemia herzogii showed branched trichomes on the gametophytes and later developed sporophytes.Conclusions: Germination in all taxa corresponds to the Anemia-type and the gametophytic development to the Ceratopteris-type. Anemia herzogii is distinguished from the two varieties by the presence of branched trichomes exclusive of the gametophytic phase. The studied taxa are characterized by the morphology of gametophyte, type of trichomes and sexuality.